2020
DOI: 10.1016/j.ebiom.2019.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation of TRIM13 in diabetic nephropathy suppresses mesangial collagen synthesis by promoting ubiquitination of CHOP

Abstract: Background: Mesangial collagen synthesis in renal glomeruli contributes to the pathogenesis of diabetic nephropathy (DN) which is one of the most serious complications of diabetes mellitus. However, the underlying mechanism of mesangial collagen synthesis is largely unknown. Methods: The differential expression of CHOP and TRIM13 which is a well-defined E3 ubiquitin ligase was compared in renal biopsy samples from DN/normal renal tissues, in isolated glomeruli of diabetic/control mice, as well as in high gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Approximately 40% of diabetic patients are prone to the development of diabetic nephropathy (DN) [ 2 4 ]. DN is one of the most common microvascular complications of diabetes and is considered the most common cause of end-stage renal disease (ESRD) [ 5 , 6 ]. Many scholars have found that some patients with diabetes and kidney disease have different clinical manifestations and sensitivities to treatment than those with typical DN [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% of diabetic patients are prone to the development of diabetic nephropathy (DN) [ 2 4 ]. DN is one of the most common microvascular complications of diabetes and is considered the most common cause of end-stage renal disease (ESRD) [ 5 , 6 ]. Many scholars have found that some patients with diabetes and kidney disease have different clinical manifestations and sensitivities to treatment than those with typical DN [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a study in vitro and vivo suggested the tripartite motif-containing (TRIM13, a well-defined E3 ubiquitin ligase) promoted ubiquitination and degradation of C/EBP homologous protein (CHOP, associated with renal injury), which attenuated DN-induced collagen synthesis and restored renal function. 82 This finding provides new insights into the application of histone ubiquitin in the treatment of diabetic nephropathy. Based on existing literature and studies, additional research is required to expose the hidden targets of histone ubiquitination to prevent DN.…”
Section: Epigenetic Modificationmentioning
confidence: 87%
“…In particular, ubiquitination and degradation of lysine-specific demethylase 3A and the downstream modulation of the TGF-β1/Smad2/Smad3 signaling induced by the plant extract magnoflorine attenuates DN and suppresses inflammatory responses and fibrosis in mesangial cells both in vitro and in vivo [ 27 ]. Mesangial collagen synthesis in DN is also modulated by the E3 ubiquitin ligase, TRIM13, by promoting ubiquitination and degradation of C/EBP homologous protein [ 28 ]. No data are available regarding the specific role of lysine 63 ubiquitination in mesangial cells under hyperglycemic conditions and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%